How Telecommunication Development Aids Economic Growth: Evidence from Itu Ict Development Index (IDI) Top Five Countries for African Region - Wilson, Ani; David, Ugwunta; Beatrice, Eneje; Mary, Okwo (International Journal of Business, Economics and Management, 2014)
This study examines the effect of telecommunication development on economic growth in five leading ICT developed countries for African region. Following previous studies, teledensity (or the penetration rate) is defined as the number of fixed-lines and mobile phone subscribers per 100 persons as a proxy to measure the development of the telecommunications sector, while economic growth is proxied by Gross domestic product at current prices (US dollars). After ensuring data stationarity, the Granger causality test shows no causal relationship between mobile and fixed teledensity and economic growth. In spite of this, the OLS test clearly shows that telecommunication development in Africa has a positive and significant influence on economic growth.